2013
DOI: 10.1371/journal.pone.0083317
|View full text |Cite
|
Sign up to set email alerts
|

The Urotensin System Is Up-Regulated in the Pre-Hypertensive Spontaneously Hypertensive Rat

Abstract: Urotensin II (UII) concentrations are raised both in humans with hypertension and in spontaneously hypertensive rats (SHR). Since the urotensin system acts to regulate glomerular filtration in the kidney it may play a greater role in the pre-hypertensive SHR in which renal dysfunction is known to precede the onset of severe hypertension. This study aimed to determine the renal actions and expression of the urotensin system in the young SHR. Intravenous rat UII (6 pmol. min-1. 100 g body weight-1) had no signif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…Consistent with this notion, in sheep, plasma UII concentrations are higher in the renal vein than in the renal artery (Charles et al, 2005), thus identifying the kidney as a source of circulating UII. In SHR, URP but not UII mRNA is elevated in kidney compared with WKY rats Forty and Ashton, 2013), suggesting a potential role for URP in spontaneous hypertension.…”
Section: H Distribution Of Urotensin II and Urotensin Ii-related Pepmentioning
confidence: 87%
See 2 more Smart Citations
“…Consistent with this notion, in sheep, plasma UII concentrations are higher in the renal vein than in the renal artery (Charles et al, 2005), thus identifying the kidney as a source of circulating UII. In SHR, URP but not UII mRNA is elevated in kidney compared with WKY rats Forty and Ashton, 2013), suggesting a potential role for URP in spontaneous hypertension.…”
Section: H Distribution Of Urotensin II and Urotensin Ii-related Pepmentioning
confidence: 87%
“…In the rat kidney, the UT gene is expressed in glomerular arterioles, thin ascending limbs, and inner medullary collecting ducts (Song et al, 2006a;Forty and Ashton, 2013). Quantitative receptor autoradiography confirms the presence of […”
Section: F Distribution Of Urotensin II Receptor In Peripheral Organsmentioning
confidence: 92%
See 1 more Smart Citation
“…Human U-II has been characterized as the most forceful arterial vasoconstrictors with 10–100 times more potent than endothelin-1 [ 5 ]. Large amount of data has demonstrated that the concentration of plasma human U-II is elevated in the cardiovascular diseases such as heart failure [ 6 ], atherosclerosis [ 7 ], hypertension [ 8 9 ], ischemia [ 10 ], chronic hypoxia [ 11 ]. Moreover, serum human U-II level was positively correlated with the degree of myocardium injury in a rat myocardial infarction model.…”
Section: Introductionmentioning
confidence: 99%
“…Studies in mice have shown similar UII and URP expression in the nervous system, skeletal muscle, testes, vagina, and gall bladder, and differential expression in the seminal vesicles, heart, colon, and thymus (Dubessy et al, 2008 ). Another study of spontaneously hypertensive rats found elevated URP mRNA expression, suggesting a potential role for URP in spontaneous hypertension (Forty and Ashton, 2013 ). The differential cellular expression of URP in unstable vs. stable carotid atherosclerosis suggests that this may occur as either cause or effect in atherosclerotic disease and warrants further investigation.…”
Section: Discussionmentioning
confidence: 99%